Beyond Revolving Doors: The Prevention of Conflicts of Interests Through Regulation. (2nd October 2017) - Cerrillo-i-Martínez, Agustí
Abstract : The revolving doors phenomenon (i.e., the movement of professionals from government and public administration to private companies or social entities) produces conflicts of interest and the possibility of corruption. It has increasingly drawn attention because of the numerous scandals that have come under the public spotlight. This article analyzes the risks the revolving door poses to public integrity and explores different mechanisms to prevent conflicts of interest. Analysis of Spain's legal mechanisms to combat the revolving door highlights the limitations of current regulations. New mechanisms are proposed that could strengthen the integrity of current public officials and of former officials who have left the public sector.